Effects of Homemade Nano-Hydroxyapatite and Olive Oil Paste on Remineralization of Early Caries Lesions - Ayşe Dina Erdilek; Sevdiye Burke; Merve Şahin; Ata Efes; Begüm Güray Efes (Baiman Bauntung Batuah Center, 2022)
Nano-hydroxyapatite (nHAP) particles are a new generation of materials reported to remineralize enamel lesions. The purpose we aimed was to compare the in vitro effects of fluoride gel, sodium fluoride toothpaste, and homemade nHAP paste on remineralizing artificial early enamel caries. Methods: Incipient caries were induced in 21 extracted, sound premolar teeth by storing each specimen in a demineralization solution for 72 hours, followed by pH cycling. The samples (n= 7, each) were then treated with 2% neutral fluoride gel, 0.25% sodium fluoride toothpaste, or homemade nHAP paste, comprising a mixture of nHAP powder and olive oil. After demineralization and remineralization, the results were compared using the DIAGNOdent pen (KaVo, Germany). The data were statistically analyzed using paired t-tests and a one-way ANOVA test. Outcomes: The degree of demineralization in each of the three groups (fluoride gel group, 15.71; sodium fluoride dentifrice group, 15.28; nHAP paste group, 16.71) was significantly elevated compared to baseline (3, 2.5, 2.28, respectively); however, no significant difference was observed between the remineralization readings in each of the three groups (6, 7, 5.5, respectively) (p > 0.05). In conclusion, we concluded that the homemade nHAP paste had a beneficial effect on the remineralization of initial enamel caries lesions.